The Study Of Kirchchoff Law And Inverse Matrix For Electrical Network Solutions - Ulul Ilmi (Universitas Islam Lamongan, 2018)
In this study the electricity network discussed was a very simple electricity network using Matlab. Matlab makes it easy for users to find assistance in connection with all the facilities provided by Matlab. For example, help on how to start Matlab for the first time, programming tricks, creating 2 and 3-dimensional graphics, using data acquisition tools, signal processing, solving partial differential equations. Power grid problems can be solved using elementary line operations and besides being solved by using elementary line operations, electricity networks can also be solved using inverse matrix